2015
DOI: 10.1363/intsexrephea.41.4.0182
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Broader Sexual and Reproductive Health Needs of Female Sex Workers In Dhaka, Bangladesh

Abstract: Female sex workers in Dhaka need family planning and other sexual and reproductive health services and prefer receiving them from drop-in centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…). For example, a study of FSWs in Bangladesh found that 25 percent of hotel‐based FSWs and 36 percent of street‐based FSWs have unmet need for family planning (Katz ). Similar trends are observed in Africa.…”
Section: Unmet Need Unintended Pregnancy and Termination Of Pregnancymentioning
confidence: 99%
“…). For example, a study of FSWs in Bangladesh found that 25 percent of hotel‐based FSWs and 36 percent of street‐based FSWs have unmet need for family planning (Katz ). Similar trends are observed in Africa.…”
Section: Unmet Need Unintended Pregnancy and Termination Of Pregnancymentioning
confidence: 99%
“…FSWs are also ostracized by the community besides suffering legal and human rights violations thereby necessitating clandestine operations that often prevent them from accessing and/or using formal health services [4]. A qualitative study on the psychological stressors in the context of commercial sex in China showed FSWs face a host of stressors precipitated by poverty, unemployment, lack of social protection, violence from clients, and limited social support from peers and stable partners [5].…”
Section: Introductionmentioning
confidence: 99%
“…Unprotected sex further complicates the reproductive health needs of FSWs by predisposing them to abortion and other associated the risk factors. In Asia and Africa, for example, the prevalence of abortion among FSWs range between 22 and 86%, a pointer that FSWs’ pregnancies are ill attended [4]. A study among FSWs in Zambia showed that women who reported a lifetime pregnancy also had a history of unplanned pregnancy, depicting a large unmet need for contraception among FSWs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Current programmes providing PrEP to FSWs are predominantly implemented through FSW‐focused services, which include drop‐in centres and clinics led by community‐based organizations . Acceptability studies indicate that these focused services are often the preferred way for FSWs to access healthcare due to staff friendliness, lower cost, shorter waiting times, privacy, proximity to places of work and greater quality of care . There are several advantages of building upon this model for integrated PrEP and family planning delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of effective non‐barrier contraception methods among FSWs is sub‐optimal, resulting in high rates of unintended pregnancy . Similarly, FSWs’ condom use, even when the primary method of pregnancy prevention, is often inconsistent, particularly with non‐paying partners .…”
Section: Introductionmentioning
confidence: 99%